2018
DOI: 10.1371/journal.pone.0205039
|View full text |Cite
|
Sign up to set email alerts
|

Cynomolgus monkeys (Macaca fascicularis) experimentally and naturally infected with hepatitis E virus: The bone marrow as a possible new viral target

Abstract: Hepatitis E virus (HEV) transmission through infected blood and blood products has already been described. However, little is known about the bone marrow (BM) as source of HEV infection. Our study aimed to investigate the presence of HEV antigen (Ag) and histological changes in BM of cynomolgus monkeys (Macaca fascicularis) experimentally and naturally infected with HEV. Four cynomolgus monkeys with acute, and two with chronic hepatitis E ─ after immunosuppressive therapy with tacrolimus ─ were compared with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The constant detection of HEV ORF2 proteins, the capsid proteins, in bone marrow suggests that HEV may replicate in the bone marrow cells. Very recently, an animal study found that HEV antigens can be detected in the bone marrow of both HEV genotype 3 experimentally infected or naturally infected cynomolgus monkeys [8]. The present study, along with the previous study conducted in cynomolgus monkeys, reinforces the assumption of bone marrow as a new HEV target.…”
supporting
confidence: 87%
“…The constant detection of HEV ORF2 proteins, the capsid proteins, in bone marrow suggests that HEV may replicate in the bone marrow cells. Very recently, an animal study found that HEV antigens can be detected in the bone marrow of both HEV genotype 3 experimentally infected or naturally infected cynomolgus monkeys [8]. The present study, along with the previous study conducted in cynomolgus monkeys, reinforces the assumption of bone marrow as a new HEV target.…”
supporting
confidence: 87%
“…In addition, there is increasing evidence to suggest that HEV also replicates in extrahepatic tissues like the kidneys. Previous studies have detected HEV RNA and antigen in the urine of patients with acute and chronic infections as well as in the kidneys of artificially infected cynomolgus monkeys [ 12 , 13 ]. Viral replication has also been demonstrated in the kidneys of infected rabbits by detection of both positive and negative strands of HEV RNA as well as by immunohistochemical analysis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past years there has been an interest in studying HEV infection in non-human primates, inclusively Macaca fascicularis were used on experimental in vivo studies performed in Brazil to evaluate HEV pathogenesis [ 91 , 92 , 93 ]. HEV seroprevalences have been reported in farmed Rhesus monkeys in China (70.8%) [ 94 ] and in captive non-human primates in Italy (4.2%) [ 95 ] but the only seroprevalence study performed in Brazil in wild non-human primates did not detect any (0%) anti-HEV antibodies [ 11 ].…”
Section: Discussionmentioning
confidence: 99%